2001
DOI: 10.1046/j.1365-2788.2001.00293.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual abuse in children and adolescents with intellectual disability

Abstract: The present authors conducted a study of the occurrence of victimization and the perpetration of sexual abuse among 43 in-patients with intellectual disability aged between 9 and 21 years who were admitted to a child and adolescent psychiatric in-patient department over a period of 5 years. A retrospective case-note review was employed that explored the nature and severity of abuse in relation to the age, gender and level of disability. The prevalence of abuse or abusive behaviour, i.e. 14% of 300 admissions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 15 publications
0
83
0
4
Order By: Relevance
“…The suggestion would simply be that male learners are expected to exhibit dominant and sexually violent behaviour while female learners are expected to be tolerant and submissive (Leach 2003). Being a female with mild intellectual disability worsens the situation, because they rarely receive treatment equal to their counterparts without disability because of common assumptions that they are unable to tell right and wrong, and that they cannot be credible witnesses (Balogh et al 2001) As revealed by Human Rights Watch (2001), the problem could push females into dropping out from school and/or absenteeism as a strategy to evade the problem, and thus further undermine their chances of accessing the curriculum on the same level as their male counterparts. Generally, learners with intellectual disabilities have less chance of access to school due to lack of infrastructural facilities in most developing countries and teachers' reluctance to admit those learners in ordinary schools (UNESCO 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The suggestion would simply be that male learners are expected to exhibit dominant and sexually violent behaviour while female learners are expected to be tolerant and submissive (Leach 2003). Being a female with mild intellectual disability worsens the situation, because they rarely receive treatment equal to their counterparts without disability because of common assumptions that they are unable to tell right and wrong, and that they cannot be credible witnesses (Balogh et al 2001) As revealed by Human Rights Watch (2001), the problem could push females into dropping out from school and/or absenteeism as a strategy to evade the problem, and thus further undermine their chances of accessing the curriculum on the same level as their male counterparts. Generally, learners with intellectual disabilities have less chance of access to school due to lack of infrastructural facilities in most developing countries and teachers' reluctance to admit those learners in ordinary schools (UNESCO 1994).…”
Section: Discussionmentioning
confidence: 99%
“…There is still limited research available to assess what, if any, differences there are among CSA victims with and without developmental disabilities (Balogh et al, 2001). In a sample researched by Balogh et al (2001), it appeared that, among adolescents with intellectual disability, females were more likely than males to have experienced sexual abuse. Mansell et al (1998) reported that CSA victims who also have a developmental disability show greater behavioral problems than do victims without developmental disability.…”
Section: Developmental Disabilitymentioning
confidence: 99%
“…Apesar da inegável vulnerabilidade destes adolescentes, principalmente nos que apresentam um nível maior de comprometimento, não existem dados que sustentem a proposição de que o abuso sexual seja mais provável de ocorrer entre pessoas com deficiência (Balogh et al ., 2001). Questiona-se se a inexistência de dados não seria conseqüência da ausência de detecção e denúncia do abuso porque, muito freqüentemente, os agressores estão entre seus familiares e cuidadores (Rimmerman & Duvdevani, 1996;McKinlay et al ., 1996;Waldman et al ., 1999).…”
Section: Abuso Sexual Contracepção E Esterilização: Debate Polêmicounclassified